Nutrition periodization for athletes. Taking traditional sports nutrition to the next level - Seebohar, B. (Bull Publ. Company, 2011)
Discover the `new school` approach - an innovative method that allows you to enlist nutrition as your ally and discover the benefits of a year-round, periodized nutrition plan.